Human Papillomavirus Infections are Common and Predict Mortality in a Retrospective Cohort Study of Taiwanese Patients With Oral Cavity Cancer. Issue 47 (November 2015) - Lee, Li-Ang; Huang, Chung-Guei; Tsao, Kuo-Chien; Liao, Chun-Ta; Kang, Chung-Jan; Chang, Kai-Ping; Huang, Shiang-Fu; Chen, I-How; Fang, Tuan-Jen; Li, Hsueh-Yu; Yang, Shu-Li; Lee, Li-Yu; et al.
Abstract : Abstract: Human papillomavirus (HPV) infections are deemed to play a role in the pathogenesis of oral cavity cancer (OCC). However, their exact prevalence and clinical significance remain unclear. Herein, we investigated the prevalence and prognostic value of HPV infections in a large sample of Taiwanese OCC patients. This study was designed as a retrospective cohort study. Between 2004 and 2011, we identified 1002 consecutive patients with newly diagnosed OCC who were scheduled for standard treatment. HPV genotyping was performed in tumor specimens using polymerase chain reaction-based HPV blots. To investigate the temporal trends of HPV infections and their impact on 5-year overall survival (OS), patients were divided into 2 cohorts according to calendar periods: "2004 cohort" (2004–2007; n = 466) and "2008 cohort" (2008–2011; n = 536). Univariate and multivariate Cox regression models were also used to identify the independent predictors of OS in the 2 cohorts. A weighted risk score was assigned to each factor based on the range of their corresponding hazard ratios and validated in both cohorts using the c-statistic. The overall prevalence of HPV infections was 19%, with a trend toward decreasing rates from 2004 to 2011. In patients without risky oral habits, the 5-year OS rate of HPV-positive patients was significantly lower than that of HPV-negative cases (49% vs 80%; P = 0.021). In the 2004 cohort, multivariate analysis identified HPV16, pathological T3/T4, pathological N1/N2, and extracapsular spread as independent adverse prognostic factors for OS. In the 2008 cohort, pathological N1/N2, pathological stage III/IV, and histological tumor depth >8 mm were identified as independent adverse prognostic factors. Using a weighted grading system incorporating HPV16 infection, we devised a prognostic index that identified 4 distinct risk categories with 5-year OS rates ranging from 25% to 89% (c-statistic = 0.76) in the 2004 cohort. The validity of the index was internally confirmed in the 2008 cohort (c-statistic = 0.71). We conclude that HPV infections are common in Taiwanese OCC patients and predict 5-year OS. If independently validated, our composite prognostic score comprising HPV16 infection may be useful for allocating OCC patients to risk-adapted therapies.